The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4269/ajtmh.14-0506
|View full text |Cite
|
Sign up to set email alerts
|

Cysticercosis-Related Hospitalizations in the United States, 1998–2011

Abstract: Abstract. Cysticercosis has become increasingly recognized as an important infection in the United States in recent decades. Despite its potential impact, there is a lack of comprehensive information on the nationwide burden of disease. To better define the burden of cysticercosis in the United States, we analyzed in-patient records using the Nationwide Inpatient Sample for 1998-2011 to estimate cysticercosis-related hospitalizations and patient/institutional characteristics. There were an estimated 33,060 (95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 23 publications
0
18
0
2
Order By: Relevance
“…The zoonotic disease complex Taenia solium taeniasis/cysticercosis (CC) causes important monetary and nonmonetary burden in endemic areas 1 5 as well as in countries where the life cycle is unlikely to be completed, such as the United States. 6 In its most severe form, T. solium cysticerci establish in the brain, causing a condition called neurocysticercosis (NCC), characterized by a range of neurological symptoms and signs, the most common being epilepsy, severe chronic headaches, and focal deficits. 7 Overall, T. solium has been estimated to incur the largest number disability-adjusted life years among foodborne parasitic infections globally.…”
Section: Introductionmentioning
confidence: 99%
“…The zoonotic disease complex Taenia solium taeniasis/cysticercosis (CC) causes important monetary and nonmonetary burden in endemic areas 1 5 as well as in countries where the life cycle is unlikely to be completed, such as the United States. 6 In its most severe form, T. solium cysticerci establish in the brain, causing a condition called neurocysticercosis (NCC), characterized by a range of neurological symptoms and signs, the most common being epilepsy, severe chronic headaches, and focal deficits. 7 Overall, T. solium has been estimated to incur the largest number disability-adjusted life years among foodborne parasitic infections globally.…”
Section: Introductionmentioning
confidence: 99%
“…NCC is the most important cause of late onset epilepsy worldwide and a growing problem in developed countries because of immigration from endemic zones. 1,2 Humans get infected by accidental ingestion of T. solium eggs excreted with the feces of human tapeworm carriers. The oncospheres are liberated from the eggs, cross the intestinal wall, and are carried by the circulatory system to almost any organ or tissue, where they develop as the larval stage or cysticercus.…”
Section: Introductionmentioning
confidence: 99%
“…9 As previous studies have shown, the use of the NIS can be useful when quantifying domestic burdens of tropical parasitic diseases in a large sample size. 37 Our results demonstrate 58 patients a year are admitted with a diagnosis of lymphatic filariasis in the United States and that the incidence is slowly rising (Figure 4). More cases were seen in the East North Central states than expected (P = 0.032).…”
Section: Discussionmentioning
confidence: 66%